Generation of spin currents by a temperature gradient in a two-terminal device - Rafael E. Barfknecht (Nature Portfolio, 2021)
Spin caloritronics exploits the effect of temperature on spin currents with a focus on features such as spin dependent thermal conductance, which are ideally suited for next generation spintronic devices. Here, the authors theoretically investigate a cold atom simulator of spin caloritronics comprising a one-dimensional spin chain between two temperature reservoirs and consider the dynamics of a spin impurity (spin flip) introduced into the chain.